(untitled) (Biological Sciences - PJSIR, 2008)
. Natural walnut dye was extracted from walnut bark and applied to cotton, woolen and silk fabrics with the same depth of colour and colour fastness was assessed. Walnut dye had good saturation on all the three fabrics and its colour fastness properties ranged between good and excellent.